Reconstructing Flexing Behavior on Social Media Through Media Ethics, Local Culture, and Religion - Rana Tsabitah; Eko Hero; Bunga Astini (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
Flexing on social media is often reduced to narcissistic and consumptive self-display, obscuring its communicative, cultural, and ethical complexity. Existing studies largely rely on psychological and consumerist perspectives, with limited attention to flexing as an ethically contingent communicative practice embedded in cultural and religious frameworks. This study addresses this gap by reconstructing flexing through the integration of media ethics, local cultural values, and Islamic moral principles. Using a qualitative Narrative Literature Review (NLR), the study synthesizes interdisciplinary literature (2021–2025) sourced from major academic databases and search engines. Analysis was conducted through conceptual extraction, thematic clustering, interpretative comparison, and integrative reconstruction. The findings identify five forms of flexing (material, prestige, aesthetic, soft, and moral), three contextual factors shaping its evaluation (digital-ethical structures, cultural values, and religious media ethics), and cross-temporal continuity in status display practices. The study proposes ethical flexing as a context-sensitive form of digital self-presentation defined by authenticity, proportionality, and social responsibility. This framework shifts the discourse from moral labeling to negotiated ethical evaluation within digitally mediated visibility systems. Flexing di media sosial sering direduksi sebagai perilaku narsistik dan konsumtif, sehingga mengabaikan kompleksitas komunikatif, kultural, dan etisnya. Kajian sebelumnya didominasi pendekatan psikologis dan konsumerisme, sementara analisis sebagai praktik komunikatif yang bergantung pada konteks etika, budaya, dan agama masih terbatas. Penelitian ini merekonstruksi makna flexing melalui integrasi etika media, nilai budaya lokal, dan moral Islam. Dengan pendekatan kualitatif melalui Narrative Literature Review (NLR), studi ini mensintesis literatur interdisipliner (2021–2025) dari basis data akademik dan mesin pencari ilmiah. Analisis dilakukan melalui ekstraksi konsep, pengelompokan tematik, perbandingan interpretatif, dan rekonstruksi integratif. Hasil menunjukkan lima bentuk flexing (material, prestise, estetika, soft, dan moral), tiga faktor kontekstual (struktur etika digital, nilai budaya, dan etika media Islam), serta kesinambungan historis dalam praktik display status. Studi ini mengusulkan konsep ethical flexing sebagai bentuk presentasi diri digital yang kontekstual, ditandai oleh autentisitas, proporsionalitas, dan tanggung jawab sosial, serta menggeser diskursus dari pelabelan moral menuju negosiasi etis.